(untitled) (Journal of Economic Research & Business Administration, 2022)
Currently, strategic planning of state policy is formed in accordance with the needs of society and socio-economic conditions. The pandemic of Covid-19 coronavirus infection caused significant damage to small and medium-sized businesses in Kazakhstan and was a realized uncertainty, setting new tasks for state policy. The purpose of this article is to analyze the features of state policy to support small and medium–sized businesses in conditions of uncertainty. In this work, a set of research methods is applied, including a sociological survey among representatives of small and medium-sized businesses and subsequent regression analysis of its results. During the analysis, the high need of entrepreneurs for state support measures, especially in financial instruments in the form of preferential loans, tax deferrals, was revealed. The study showed insufficient access of small and medium-sized businesses to information on government support measures. Based on the results of the regression analysis, the factors of influence on the assessment by representatives of small and medium-sized businesses of the state policy in relation to them were established. The results of this study can be applied in the development of state policy to support small and medium-sized businesses. Key words: state policy, small and medium-sized businesses, state support, uncertainty